Potentially inappropriate prescribing in Ethiopian geriatric patients hospitalized with cardiovascular disorders using START/STOPP criteria - Abegaz, Tadesse Melaku; Birru, Eshetie Melese; Mekonnen, Gashaw Binega (PloS one, 2018)
There was a paucity of data on the magnitude of potentially inappropriate prescriptions (PIPs) among Ethiopian elderly cardiovascular patients. The aim of this study was to assess PIPs and associated factors in the elderly population with cardiovascular disorders using the START/STOPP screening criteria. A hospital-based cross-sectional study was conducted at medical wards of a teaching hospital in Ethiopia from 1 December 2016-30 May 2017. Included patients were hospitalized elderly patients aged 65 years or older with cardiovascular disorders; their medications were evaluated using the START/STOPP screening criteria from admission to discharge. Multivariable logistic regression was applied to identify factors associated with inappropriate medications. One Way Analysis Of Variance (ANOVA) was carried out to test significant differences on the number of PIPs per individual diagnosis. Two hundred thirty-nine patients were included in the analysis. More-than a third of the patients were diagnosed with heart failure, 88 (36.82%). A total of 221 PIPs were identified in 147 patients, resulting in PIP prevalence of 61.5% in the elderly population. Of the total number of PIPs, occurrence of one, two and three PIPs accounted for 83 (56.4%), 52(35.4%), and 12(8.2%) respectively. One way ANOVA test showed significant differences on the mean number of PIPs per individual diagnosis (f = 5.718, p<0.001). Angiotensin Converting Enzyme Inhibitors (ACEIs) were the most common inappropriately prescribed medications, 32(14.5%). Hospital stay, AOR: 1.086 (1.016-1.160), number of medications at discharge, AOR: 1.924 (1.217-3.041) and the presence of co-morbidities, AOR: 3.127 (1.706-5.733) increased the likelihood of PIP. Approximately, two-thirds of elderly cardiovascular patients encountered potentially inappropriate prescriptions. ACEIs were the most commonly mis-prescribed medications. Longer hospital stay, presence of comorbidities and prescription of large number of medications at discharge have been correlated with the occurrence of inappropriate medication. It is essential to evaluate patients' medications during hospital stay using the STOPP and START tool to reduce PIPs.